Analisis daya saing ubi jalar di kabupaten Karanganyar - Ardina Nur Halimah; Endang Siti Rahayu; Ernoiz Antriyandarti (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
Sweet potato is a food crop that is easily found and easy to cultivate, can be used as a substitute good for rice and maize. This study aims to determine the competitive and comparative advantages of sweet potato farming and to analyze government policies and their relation to the competitiveness of sweet potato farming in the Karanganyar district. The data analysis method used is the Policy Analysis Matrix (PAM) method. The determination of the sample areas was carried out deliberately in the Tawangmangu, Ngargoyoso, and Jumantono Districts, Karanganyar Regency. The respondents were 60 farmers. The results showed that the private profit was IDR 22,459,017.68 and a PCR value of 0.49, then the social benefit is IDR 71,826,979.74 and a DRCR value of 0.23 which means that the sweet potato commodity also has a competitive and comparative advantage. The output policy parameter consists of an output transfer of –IDR 49,894,031.87 and an NPCO ratio of 0.48, which means output policy has not been effective, indicated by the low domestic sweet potato price. The Input policy parameters consist of an Input transfer value of –IDR 804,269.45, an NPCI ratio of 0.54, and a factor transfer value of IDR 278,199.64, which means Input policy has protection from the government, fertilizer subsidies, and non-tradeable Inputs subject to land tax. The Input-output policy parameters consist of a net transfer of IDR 49,367,962.06, an EPC value of 0.48, and an SRP value of -0.52, which means the Input-output policy has not been provided economic incentives, as a result, farmers spend higher production costs.